2005
DOI: 10.1249/01.mss.0000155437.45937.82
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Level is Associated with the O2 Cost of Walking in Cerebral Palsy

Abstract: For this population, those with low PAL may also have a high oxygen cost of walking. These individuals' PAL was not related to their peak VO2. Further research is required to determine whether interventions that decrease the oxygen cost of walking also affect PAL and whether changes in PAL affect the oxygen cost of walking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
92
3
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(102 citation statements)
references
References 20 publications
4
92
3
1
Order By: Relevance
“…Maltais et al, have recently used an activity monitor to assess habitual physical activity in 11 children with mild CP, in an attempt to determine the relationship between physical activity and biomechanical treadmill walking economy. In addition this group recently used HR monitoring to assess physical activity level in children with CP in a protocol designed to determine relationship between physical activity and cost of walking.The study suggests that children with low physical activity levels may have a higher energy cost of walking [39,40].…”
Section: Discussionmentioning
confidence: 87%
“…Maltais et al, have recently used an activity monitor to assess habitual physical activity in 11 children with mild CP, in an attempt to determine the relationship between physical activity and biomechanical treadmill walking economy. In addition this group recently used HR monitoring to assess physical activity level in children with CP in a protocol designed to determine relationship between physical activity and cost of walking.The study suggests that children with low physical activity levels may have a higher energy cost of walking [39,40].…”
Section: Discussionmentioning
confidence: 87%
“…Aerobic fitness of children or athletes with cerebral palsy has been vigorously investigated by Bar-Or 10) , Fernandez et al 23,24) , Lundberg 25,26) , Maltais et al [27][28][29][30] , van den Berg-Emons et al [31][32][33][34] , and other researchers since the 1960s. These studies were based on work physiology that was mainly established by Åstrand et al 9) .…”
Section: History Of Research On Aerobic Fitness In Individuals With Cmentioning
confidence: 99%
“…This work physiology was originally intended to provide practical information to athletes to improve their performance. Since the 1960s, physiological studies have mostly focused on the wellness of children 3,10,[25][26][27][28][31][32][33][34][35][36][37][38][39][40][41][42][43] or athletes [44][45][46][47][48][49][50][51][52][53][54] with cerebral palsy mainly rated to Gross Motor Function Classification System (GMFCS) level I or II. In the late twentieth century, many new remedies proliferated one after another in an attempt to recover loss of function in children with cerebral palsy.…”
Section: History Of Research On Aerobic Fitness In Individuals With Cmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Moreover, studies using these protocols with children and adolescents with CP reported no adverse health or safety effects. 4,19,24,[37][38][39] Thus, one can conclude that in general, with the proper safety precautions as described by Paridon et al, 35 maximal exercise testing for children and adolescents with CP is suitable and safe.…”
Section: Recommendations For Clinical Practicementioning
confidence: 99%